Adsorption of Carbon Monoxide (CO) in ZSM-5 Membrane on Smoking Area - Azizah I.H.; Fannya G.R.; Mindhumalid T (Universitas Muhammadiyah Semarang, 2017)
This research aims to know the ability of ZSM-5 adsorbed on the cigarette smoke so that it can reduce the levelsof CO in the smoking area. Zeolite membranes formed from steel AlSi316 gauze covered with ZSM-5 prekusor with size of 5 cm, 4 cm, 3 cm, 2 cm and 1 cm are kept at a temperature of 900C for 4 days then characterizedusing x-ray diffraction (XRD), FTR and SEM, with absorbance test place the gauze into the enclosed spacevolume 18.000 cm3 containing CO from cigarette smoke.The research was recently reached the stage ofinorganic and organic substances leaching and oxidized in electrochemistry in H2SO4 to 20% We use the result of the previous research by title Adsorption test of Carbon monoxide using Lampung and Malang natural zeolite, by Aditya Zulfa. In that research, Malang and Lampung natural zeolite are being tested its adsorption capacity of CO in pressure condition 0 to 178 psia with 25 psi interval and using variation of adsorbent size and adsorbtion temperature. Both of those zeolites are being compared its adsorbtion capacity, before and after the activation process.The result of Lampung natural zeolite which has the highest adsorption capacity CO, 0,5866 mmol/g at 175 psia. So, it can be found the best specification of an adsorbent which has the highest adsorption capacity of CO between two of natural zeolite. Keywords: Adsorption, Carbon Monoxide (CO), ZSM-5 Membrane, Smoking Area